Biogenesis - Lahav, Noam (Oxford University Press, 1999)
The book begins with the history of the search for life's origin from the Greek philosophers to contemporary scientists. The author introduces the reader to important aspects of scientific thinking, and covers the biases, successes, and failures of these thinkers. Part II succinctly describes selected attributes of life, which are connected to theories and controversies of the studies of the origin of life. The main features of the solar system and Earth, where life is assumed to have originated, are briefly reviewed in Part III. This section covers the formation of the planet, its primordial atmosphere and seas, and the Gaia theory. Part IV investigates the rationale of the scientific theories of the origin of life